STEAM approach in project-based learning to develop mathematical literacy and students' character - Supianti, In In; Yaniawati, Poppy; Bonyah, Ebenezer; Hasbiah, Astri Widiastuti; Rozalini, Nisrina (IKIP Siliwangi and I-MES, 2025)
Mathematics is essential for individuals to solve everyday life problems. However, students remain insufficiently motivated in mathematics learning, necessitating the implementation of engaging teaching approaches integrated with other disciplines, such as STEAM (Science, Technology, Engineering, Art, and Mathematics). This study investigated the effectiveness of a STEAM-based Project-Based Learning (PjBL) approach on mathematical literacy and character development among secondary school students. Utilizing a mixed-methods convergent parallel design, the research employed quantitative and qualitative techniques. The quantitative data collection used a literacy skills test to measure mathematical literacy. Meanwhile, the qualitative data collection to measure students' character utilized surveys, interviews, and observations. Quantitative data analysis was conducted using the Kruskal-Wallis test, while qualitative data analysis employed triangulation, including data reduction, data presentation, and data verification stages. The study results revealed that students' mathematical literacy significantly improved after participating in STEAM-PjBL-based learning. Additionally, STEAM-PjBL fosters the development of students' character traits, including teamwork, communication, and responsibility, highlighting its potential to support holistic educational outcomes. These findings indicate that integrating STEAM principles with PjBL enhances academic performance and cultivates critical 21st-century skills.